Genetic Basis of Yield Variation in Spring Mung Bean (Vigna radiata L.): A Correlation and Path Analysis Study - Mukesh; Yumnam, Sonika; Laishram, Priyashree; Kumar, Harish; Senjam, Pushparani; Khomba Singh, L. Nongdren; Gopimohan, N.; Jat, Jitendra Kumar (International Journal of Bio-resource and Stress Management, 2024)
The investigation was conducted in March to June, 2022 at CAU research farm Andro, Imphal East, Manipur, India to study the nature, magnitude and interrelationships of genetic variation present within various characters of mung bean. This study included 27 mung bean genotypes in a Randomized Block Design with three replications. Analysis of variance revealed significant genetic variation (p<0.01) for all studied traits. Phenotypic coefficient of variation (PCV) values was higher than genotypic coefficient of variation (GCV) values, indicating some environmental influence on trait expression. High heritability (>60%) was observed for plant height, number of clusters plant-1, pod length, number of seeds plant-1, 100-seed weight, protein%, and seed yield plant-1. These traits also exhibited high genetic advance (>20%), suggesting a significant role of additive gene effects. Seed yield plant-1 displayed positive correlations with number of clusters plant-1, number of pods plant-1, pod length, number of seed pod-1 and 100-seed weight at both phenotypic and genotypic levels. Path analysis revealed that number of pods plant-1 and number of seeds pod-1 were the most significant contributors to seed yield. These findings suggest that selection for these traits, along with indirect selection for pod length, 100-seed weight, flowering time, and protein%, could be effective strategies for improving mung bean yield.